2018
DOI: 10.3390/w10040497
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Hydrological Performance of Permeable Pavement Systems in Northern Spain: An Approach to the “End-of-Life” Concept

Abstract: Porous mixtures and Interlocking Concrete Block Pavements (ICBP) are the most widely used surfaces in Permeable Pavement Systems (PPS). Despite the fact that there are many studies based on the hydrological performance of PPS, there are few long-term studies that identify the end of life of PPS regarding their hydrological performance. A field study has been developed over 10 years in the experimental car park "Las Llamas" in the city of Santander, Northern Spain. Permeability was measured in 37 car park bays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 20 publications
1
15
0
3
Order By: Relevance
“…Some works show evidence of obstruction after 4 years of operation [ 35 ] and 6 years [ 33 ], so, in the ‘middle-term’, clogging may appear, and maintenance operations will be required. Other papers confirm major obstructions in the ‘long-term’, starting from 10 years [ 29 ] or 12 years [ 36 ]. Different climatic conditions may be the origin of these differences, so it is not yet possible to draw definitive conclusions about the ‘end of life’ of these systems.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Some works show evidence of obstruction after 4 years of operation [ 35 ] and 6 years [ 33 ], so, in the ‘middle-term’, clogging may appear, and maintenance operations will be required. Other papers confirm major obstructions in the ‘long-term’, starting from 10 years [ 29 ] or 12 years [ 36 ]. Different climatic conditions may be the origin of these differences, so it is not yet possible to draw definitive conclusions about the ‘end of life’ of these systems.…”
Section: Introductionmentioning
confidence: 88%
“…The recent start-up of many SuDS projects, and the lack of monitoring of their performance during the operational phase, results in a lack of data on the evolution of their efficiency over time. As some studies [ 28 , 29 ] indicate, more information is needed to optimize the operation of these systems, identifying the ‘end of life’ and when maintenance may be necessary to restore permeability and hydrological functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Sanudo-Fontaneda et al proposed an "end-of-life" concept based on the long-term hydrological performance of permeable pavement systems in northern Spain. The research showed that, after 10 years of operation without maintenance, the bays constructed using porous mixtures were completely clogged, reaching the end of their operational life after nine years [26]. Razzaghmanesh and Beecham investigated this mechanism through surface infiltration methods, the use of embedded sensors, and the development of modelling tools.…”
Section: Introductionmentioning
confidence: 99%
“…As these pollutants are being trapped within the joints and layers of the permeable pavement, the drainage performance of the pavement is at risk of failure, until it finally reaches an unacceptable level [6,9,12]. To better understand the clogging and filtration processes within permeable pavements, many studies have been conducted to assess the long-term hydraulic capacity through field and laboratory experiments [6,[13][14][15][16][17][18][19].…”
Section: Pollutant Removal (%)mentioning
confidence: 99%